DIGITAL LEADERSHIP IN PUBLIC SERVICE TRANSFORMATION IN THE SMART CITY ERA - Ananda, Putri Dera (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Bureaucracy, as an administrative apparatus of government, plays a crucial role in achieving good, efficient, and accountable governance. Accountability in bureaucracy refers to the government's ability to justify its decisions and policies to the public. With the rapid development of technology, the implementation of e-government, big data, and blockchain offers opportunities to improve transparency and efficiency within the bureaucratic system. However, despite the immense potential of technology, major challenges remain, such as limited infrastructure, disparities in technological access, and bureaucratic resistance to change. Additionally, the persistent practices of corruption, collusion, and nepotism (KKN) in some government sectors hinder the creation of an accountable bureaucracy. Therefore, it is crucial for the government to carry out reforms in human resource management, technological infrastructure, and organizational culture. This study aims to explore the role of technology in enhancing bureaucratic accountability in Indonesia and provide policy recommendations for improving governance practices to be more transparent and accountable.